Instruction on Creating Interactive Quizzes Using Mentimeter Application in Civics Education Learning - Jamaludin Jamaludin; Shofia Nurun Alanur; Windy Makmur; Nasran Nasran; Sunarto Amus (Universitas Lambung Mangkurat, 2024)
This community service activity is grounded in the challenge that teachers face when teaching civics education in the classroom, given the students' circumstances and confronted with the necessity to adjust to education in the twenty-first century, which is based on technology and information aligning with the Merdeka curriculum. Engaging in enjoyable learning activities can facilitate students' comprehension and retention of academic material. This service activity intends to enable teachers to utilize interactive learning media in the classroom using the Mentimeter application. The community service is conducted by implementing service learning at SMA Negeri 3 Palu in collaboration with the service team. The attendees comprised representatives from both the teaching and student communities. The implementation phase comprises the coordination phase, the program implementation phase (preceded by a pre-test), material provision, teacher and student trial, and the evaluation phase (post-test). The results of the service indicated that both teachers and students were unfamiliar with the Mentimeter application prior to the activity. Following the instruction, teachers and students engaged in practical exercises. Teachers are intrigued by the prospect of incorporating this application into their lessons due to the enthusiasm of students and their fondness for the media.